Mathematical Representation of Vasorelaxant Effect ofBenzopyranes Using Box-Jenkins Model: Representation of vasorelaxant effect of benzopyranes - Sarbaz, Yashar; Babaei, Hossein; Gharibzadeh, Shahriar; Towhidkhah, Farzad; Osuli, Hamed; Soltani, Somaieh; Jouyban, Abolghasem (Iranian Journal of Pharmaceutical Sciences, 2007)
Drug design is generally achieved through trial and error methods, which is a timeand resource consuming process and novel methods are needed to improve it.Mathematical modelling is one of the possible solutions to speed up this process.In this study, we have presented Box-Jenkins model, to predict the vasorelaxantactivity (pEC50) of a set of benzopyrane compounds. We used the HyperChemsoftware to extract the molecular features of these compounds (51 molecules);then these features were used to generate the Box-Jenkins model. The dataset wasdivided into three groups: 37 for training, 9 for prediction and 5 for validation. Theabsolute relative deviation of the predicted values was 4.8% and 4.1% for validationand predicton sets, respectively. The correlation coefficient between the predictedpoints and the experimental values was 0.9657, revealing that the proposed modelis capable of representing pEC50 of benzopyranes and could be used to speed updrug discovery processes.